Лев Толстой в Польше: Материалы к библиографии (1990–2008)[Leo Tolstoy in Poland: A Very Short Bibliography (1990—2008)] - Piotrowska, Joanna (Slavica Revalensia, 2018)
This comprehensive bibliography lists 36 translations of Leo Tolstoi’s works into Polish, and over 100 publications on Tolstoi, which appeared in Poland from 1990 to 2008.